(untitled) (Technological Innovations Journal, 2024)
The rapid population growth in cities of developing countries, such as Mazatlán, Sinaloa, poses significant challenges due to the disconnection between demographic growth and economic productivity. This imbalance raises concerns about the sustainability of the population’s well-being and the socio-economic environment. This study analyzes the economic environment of Mazatlán and its impact on the social environment during the period 2018-2023, considering housing as an essential indicator of wealth and quality of life. The objective of this research is to examine how the municipality’s economic dynamics affect the quality of life of its inhabitants. To achieve this, a qualitative approach was adopted through a documentary review of secondary sources, focusing on key indicators such as Gross Domestic Product (GDP) per capita, the Economically Active Population (EAP), and housing, using data provided by official institutions such as INEGI. Among the main findings, it was observed that GDP per capita fluctuated between 154,599 in 2019 and 164,484 in 2021, while the population reached 510,186 inhabitants in 2023. Although in 2020, the proportion of the EAP with occupied housing reached 96.69%, it decreased to 95.9% in 2021, reflecting vulnerabilities in the municipality’s socio-economic dynamics. In conclusion, the impact on the social environment was limited, due to the lack of economic diversification and the negative effects of the COVID-19 pandemic. This highlights the need to implement public policies that promote the development of strategic sectors, strengthen infrastructure, and reduce social inequalities.